Transactivation response DNA‐binding protein of 43 kDa proteinopathy and lysosomal abnormalities in spastic paraplegia type 11. Issue 4 (24th May 2021) - Mori, Shinichiro; Honda, Hiroyuki; Hamasaki, Hideomi; Sasagasako, Naokazu; Suzuki, Satoshi O.; Furuya, Hirokazu; Taniwaki, Takayuki; Iwaki, Toru
Abstract : Spastic paraplegia type 11 (SPG11) is the most common autosomal recessive hereditary spastic paraplegia with thinning of the corpus callosum. Spatacsin, a protein encoded by the SPG11 gene, is associated with autophagy. SPG11 patients show spastic paraplegia, intellectual disability, dementia, and parkinsonism. A previous neuropathological analysis of SPG11 cases reported neurodegeneration mimicking amyotrophic lateral sclerosis without transactivation response DNA‐binding protein of 43 kDa (TDP‐43) deposits and unique sequestosome 1 (SQSTM1)‐positive neuronal inclusions. We performed a neuropathological examination of two Japanese patients with complicated spastic paraplegia with thinning of the corpus callosum from different families, and one was genetically diagnosed as having SPG11. Both cases showed diffuse atrophy of the brain and spinal cord. Depigmentation of the substantia nigra was also observed. Immunohistochemistry revealed widespread distribution of areas showing TDP‐43 aggregation in the central nervous system. The TDP‐43 deposits in the thalamus and substantia nigra especially resembled skein‐like inclusions. Unique SQSTM1‐positive neuronal inclusions, as previously reported, were widespread in the whole central nervous system as well as the dorsal root ganglia. Double‐labeling immunofluorescence of the dorsal root ganglia revealed that the unique, large SQSTM1‐positive cytoplasmic inclusions of the ganglion cells were labeled with lysosome‐associated membrane protein 1 and lysosome‐associated membrane protein 2. This is the first report showing TDP‐43 pathology in SPG11. The common neuropathological findings of TDP‐43–positive inclusions in both the cases imply a causal connection between the TDP‐43 proteinopathy and autophagy dysfunction in SPG11.